Kajian Pengukuran Indeks Kepuasan Masyarakat Program Corporate Social Responsibility PT. Adaro Indonesia - Taufik Arbain; Muhammad Noor; Muhammad Riyandi Firdaus; Leni Marlina; Aan Nurhadi (stiatabalong.ac.id, 2021)
Community satisfaction is a very important factor and determines the success of a business entity because the community is the consumer of the product or service it produces. This Community Satisfaction Index Research aims to measure the Community Satisfaction and Expectation Index towards the Corporate Social Responsibility Programs of PT. Adaro Indonesia in 2020 both partially and cumulatively in Education, Health, Real Income Level, Economic Independence, Social Culture, Environmental Management, Community Institutional Formation and Infrastructure Development. This research uses a mixed method approach (quantitative and qualitative) using indicators according to the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform Number 14 in 2017 concerning Guidelines for Compilation of Community Satisfaction Surveys combined with additional indicators based on pre-survey results. The variables of this Community Satisfaction Index Survey concept consist of expectations and reality, while the data collection techniques are (1) Interview, (2) Documentation, Observation and field survey, (3) Secondary Data Collection, and (4) Focus Group Discussion. The findings of the community satisfaction survey of the beneficiaries of the Corporate Social Responsibility Programs of PT. Adaro Indonesia in 2020, namely: (1) The value of the community satisfaction survey on the Corporate Social Responsibility program of PT. Adaro Indonesia in 2020 in its Operational Area achieved an average value of community satisfaction of 86,12 and the value of community expectations of 34,52 with the service quality of the Corporate Social Responsibility program of PT. Adaro Indonesia in 2020 in its operational area is included in the